2003
DOI: 10.2214/ajr.181.1.1810261
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MR Imaging of Cholesteatoma in Pediatric and Adult Patients Who Have Undergone Middle Ear Surgery

Abstract: Diffusion-weighted MR imaging combined with conventional MR imaging can confirm residual or recurrent cholesteatoma in patients who have undergone middle ear surgery by showing a high-signal-intensity lesion. Because tumors smaller than 5 mm may be missed, a diffusion-weighted MR imaging study with negative findings does not exclude small residual or recurrent cholesteatoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
3
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 16 publications
3
126
3
9
Order By: Relevance
“…Surgical treatment of the cholesteatoma is more functional and convenient when it is diagnosed earlier [1][2][3]. The surgery is less successful when the diagnosis is not clear and/or the size/location of the lesion is not exactly known [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical treatment of the cholesteatoma is more functional and convenient when it is diagnosed earlier [1][2][3]. The surgery is less successful when the diagnosis is not clear and/or the size/location of the lesion is not exactly known [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The surgery is less successful when the diagnosis is not clear and/or the size/location of the lesion is not exactly known [1][2][3][4][5]. Otoscopy, oto-endoscopy and microscopy are some of the clinical procedures used for the diagnosis of cholesteatoma [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using diffusion MRI reported high specificity levels in diagnosing cholesteatomas larger than 0.5cm (Table 1) 11,12,15,16 . Vercruysse 16 reported lower sensitivity levels due to increased prevalence of residual cholesteatomas smaller than 0.5cm in size.…”
Section: Discussionmentioning
confidence: 90%
“…Granulation tissue, fibrous tissue, cholesterol granuloma or serous fluid has a low signal intensity on DWI (at a b-factor of 800 sec/mm 2 ). Visual comparison of DWI images obtained with a b-factor of 800 sec/ mm 2 without calculation of the apparent diffusion coefficient is sufficient for diagnostic analysis [58,59]. The reason for the high signal intensity is assumed to be a T2 shine-through effect or the restricted molecular diffusion of cholesteatoma.…”
Section: Diffusion-weighted Imaging (Epi-dwi Non-epi-dwi Resolve)mentioning
confidence: 99%